PERBANDINGAN TINGKAT KESEGARAN JASMANI SISWA KELAS X SMA NEGRI 1 RENGAT BARAT DENGAN SISWA KELAS X SMA NEGRI 2 RENGAT BARAT - Dede suryana; Saripin '; Kristi agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this study began from the observation researchers that differences in physical fitness grade X SMA Negeri 1 West Rengat higher than the grade X SMAN 2 West Rengat, It can be seen during the process of teaching and learning a sport where there are still many children who complain in physical activity. Therefore, this study aimed to compare the physical fitness level of grade X SMA Negeri 1 West Rengat with grade X SMAN 2 West Rengat. This type of research is an ex post facto research. The population in this study were students of SMA Negeri 1 West Rengat consisting of 160 students and students of grade X SMAN 2 West Rengat consisting of 128 students of grade X. Sampling was done by purposive sampling, the sample in this study grade X.1 students of SMA 1 West Rengat totaling 29 people and grade X.1 students of SMA Negeri 2 West Rengat totaling 29 people, after the data is obtained, the technique of data analysis in this research is to use the test